A Financial Conditions Index for Poland - Ho, Giang (IMF Working Papers; Working Paper ;, 2013)
This paper constructs a financial conditions index for Poland to explore the link between financial conditions and real economic activity. The index in constructed by applying two complementary approaches-factor analysis and vector auto-regression approach. We evaluate the index's forecasting performance against a composite leading indicator developed by the OECD. We found that the FCI is highly correlated with GDP growth, attesting to the importance of financial sector in Poland's economy. In-sample and out-of-sample forecasting exercises indicate that the FCI can outperform the CLI in predicting near-term GDP growth.